2011
DOI: 10.2478/v10102-011-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress biomarkers and acetylcholinesterase activity in human erythrocytes exposed to clomazone (in vitro)

Abstract: The aim of this study was to investigate the effect of clomazone herbicide on oxidative stress biomarkers and acetylcholinesterase activity in human erythrocytes in in vitro conditions. The activity of catalase (CAT), superoxide dismutase (SOD) and acetylcholinesterase (AChE), as well as the levels of thiobarbituric acid reactive substances (TBARS) and reduced glutathione (GSH) were measured in human erythrocytes exposed (in vitro) to clomazone at varying concentrations in the range of 0, 100, 250 and 500 µg/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…For example, human erythrocytes have been exposed in vitro to a range of clomazone concentrations (0, 100, 250 and 500 ug/L) for 1 h to investigate effects on oxidative stress biomarkers and on AChE activity (Santi et al 2011); both AChE and catalase activities decreased with each concentration, whereas glutathione (GSH) was not affected.…”
Section: Non-target Faunamentioning
confidence: 99%
“…For example, human erythrocytes have been exposed in vitro to a range of clomazone concentrations (0, 100, 250 and 500 ug/L) for 1 h to investigate effects on oxidative stress biomarkers and on AChE activity (Santi et al 2011); both AChE and catalase activities decreased with each concentration, whereas glutathione (GSH) was not affected.…”
Section: Non-target Faunamentioning
confidence: 99%
“…Such alterations are often observed in workers from the rural environment, what can be justified by the fact that the exposure to the agrochemicals can produce a variety of biochemical injuries, such as in the connection target-cell/receptor, as well as in the enzymatic induction or inhibition (Santi et al, 2011). Therefore, the increase in TBARS and PCs in group B (Figures 1 and 2) confirm that the 2,4-D 1.1 g/L has a high toxicity in cellular level, which can cause several changes in the human body and lead to development of serious diseases, especially in the case of chronic exposure (Murussi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, pesticides pose a risk to humans especially those professionally involved in their production, the workers in agriculture and the general population which consumes contaminated food products (TROUDI et al, 2012 Thus, the widespread use of pesticides in agriculture results in continuous exposure of human populations and several studies have reported associations between the exposure to agricultural chemicals and health alterations. Low-level exposure to pesticides is known to produce a variety of biochemical changes such as target cell/receptor binding, protein and DNA adduct formation, as well as induction or inhibition of enzymes (LÓPEZ et al, 2007;SANTI et al, 2011). However, these investigations are often limited by self-reported exposures and little advance is obtained regarding the biological mechanisms linking exposure to pesticides and health outcome (MUNIZ et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Given that, lipid peroxidation (LPO), which is the major contributor to the loss of cell function, as well as DNA damage, enzyme inactivation, and hormone oxidation are indicators of oxidative cell damage (RUAS et al, 2008). LPO, in particular, has been suggested to be one of the mechanisms of pesticideinduced toxicity (MANSOUR & MOSSA, 2009;SANTI et al, 2011). On the other hand, antioxidant markers are observed by analyzing the activity of enzymes such as catalase (CAT) that is ubiquitously present in a wide range of aerobic cell types and in red blood cells where it is found as a soluble protein that may protect against peroxidation of hemoglobin.…”
Section: Introductionmentioning
confidence: 99%